NIAT PEMBELIAN SAYURAN ORGANIK DI RETAIL KOTA BEKASI (PENGEMBANGAN THEORY OF REASONED ACTION) - Muhammad Saiful Mubarok; Sumihar ML Tobing; Imas Wildan Rafiqah (Fakultas Pertanian Universitas Borobudur, 2022)
ABSTRACT Structural Equation Modeling (SEM) is a statistical modeling technique that is highly cross-sectinal, linear, and complex. SEM is a combination of two multivariate techniques, namely confirmatory factor analysis and path analysis. The purpose of this study was to analyze the effect of knowledge, health awareness, attitudes, subjective norms and perceived difficulties on the purchase value of organic vegetables in Bekasi city retail. The basic method in this research is descriptive and analytical method. The location determination method in this study was purposive. Determining the number of samples using a ratio of 20:1 where each variable must have 20 data to be tested. The sample is 120 respondents. Instrument testing and data analysis using SmartPLS 3.0 software The analysis tool used is PLS (Partial Least Square). The data analysis used covers 3 aspects, namely the outer model, inner model and hypothesis testing with the Path Coefficient method. There are 6 variables tested, namely knowledge, health awareness, attitudes, subjective norms, perceived difficulties, and purchase value. The results showed that knowledge and health consciousness had a positive effect on the attitudes of respondents in the intention to purchase organic vegetables in Bekasi city retail. Attitudes and subjective norms variables partially have a positive effect on purchase intention of organic vegetable in Bekasi city retail. While the perceived difficulty variable partially negatively influences the purchase intention of organic vegetables in Bekasi city retail. Keywords : SEM, Organic vegetable, TRA